GAMBARAN PENGETAHUAN, SIKAP DAN MOTIVASI PASIEN PADA PEMAKAIAN RETAINER PASCA FIXED ORTHODONTI DI PERFECT SMILE PEKANBARU - Natassa, Jihan; Rachmathika, Ira; Lubis, Rachman (Jurnal Keperawatan Abdurrab, 2016)
The retainer is a passive which help in dealing orthodonti which helps in correct and stabilization of teeth in a long time to provide opportunities reorganization structure-structure supporters after phase active in care orthodonti treatment. This research aims to knowing Factors-Factors Of Importance Usage Hawley Retainer Pasca Orthodonti Fixed in clinic Perfect Smile 2016. This type of research is quantitative descriptive with a totals of samples is 66 respondents in clinic Perfect Smile Pekanbaru. When the research on may-june 2016. This research was conductif by filling out a questionnaire. Results of univariate analyst status user hawley retainer there are many 13 respondents (19,7%), knowledge level against a removable retainer  good knowledge 52 respondents (78,8%) and not good 14 respondents (21,2%), attitude positive is 61 respondents (90,9%) and attitude negative 5 respondents (7,6%), motivation good is  64 respondents (97,0%), and motivation not good 3 (4,5%). Status user removable more in dominated by that do not use removable retainer, level knowledge patient in dominanted is good, attitude is positive and motivation is motivation good. Be expected the research it can be help add the knowledge is retainer and usefulness and can be reference to researchers further.